Association of maternal TSH and neonatal metabolism: A large prospective cohort study in China - Hou, Qingzhi; Zou, Hui; Zhang, Shuping; Lin, Jiujing; Nie, Wenying; Cui, Yazhou; Liu, Sijin; Han, Jinxiang (Frontiers in Endocrinology, 2022)
Aims: Neonatal metabolites are very important in neonatal disease screening, and maternal thyroid hormones play an important role in fetal and neonatal health. Our study aimed to explore the association of maternal thyroid hormones with neonatal metabolites and identify an important time windows. Methods: Pregnant women were recruited in Jinan Maternity and Child Care Hospital and followed up until delivery. Multivariate generalized linear regression models (GLMs) and restricted cubic spline (RCS) regression analysis models were used to investigate the associations of maternal TSH and FT4 with neonatal metabolites. Results: In total, 6,653 pairs of mothers and newborns were enrolled in our study. We identified 5 neonatal metabolites, including arginine/ornithine (Arg/Orn), C14:1/C2, C18:1, C3DC+C4OH and C8:1, that were significantly associated with maternal serum TSH during the whole pregnancy (P < 0.05), especially in the first trimester. Moreover, 10 neonatal metabolites were significantly associated with maternal serum FT4 (P < 0.05), most of which had positive correlations with maternal FT4 in the first trimester (P < 0.05). Some neonatal metabolites also had linear or nonlinear dose-effect relationships with maternal serum TSH and FT4 during the whole pregnancy, particularly in the first trimester. Conclusions: Our study, for the first time, provides epidemiological evidence that maternal serum TSH and FT4, especially during the first trimester, are associated with linear or nonlinear variations in neonatal metabolites. Efforts to identify newborn metabolism levels should carefully consider the effects of maternal thyroid function.